Alternative medicine devices and the making of scientific herbal medicine in Ghana. Issue 2 (3rd April 2022) - Droney, Damien
ABSTRACT: Many herbal medicine clinics in the West African nation of Ghana employ alternative medicine diagnostic equipment to help them stand out within a competitive popular medical sector. These devices are a prominent feature of clinics that identify as practising scientific herbal medicine, and they promise scientifically advanced methods of diagnosis and treatment that stand outside mainstream biomedicine. Based on ethnographic research at two such clinics, I argue that frustrations with the functionality of these devices reveal the ongoing legacies of colonialism and its aftermath in Ghanaian cultures of expertise. Alternative medicine devices were sometimes represented as objects of spectacle. However, their failure to operate as advertised engendered debates about Ghana's place in transnational technoscientific networks. Finally, access to alternative medicine devices was structured through morally ambiguous financial transactions. In these ways, the construction of scientific herbal medicine is patterned by cultural meanings of science and technology produced through legacies of Ghana's twentieth-century history.